Distribution and ecology of the four Macrourus species by‐caught in the longline fishery at South Georgia, Southern Ocean - José Abreu; Philip R. Hollyman; Jennifer J. Freer; M. L. Romero Martínez; José P. Queirós; Timothy Jones; Richard A. Phillips; José C. Xavier; Martin A. Collins (Journal of Fish Biology, 2026)
Although Macrourus species are the main by‐catch across Southern Ocean longline fisheries, including around South Georgia, the lack of species‐specific data has hindered effective management and ecological understanding. Aggregation of macrourids at genus level masks critical interspecific differences in life‐history strategies and vulnerabilities to fishing. Here, we provide the first comprehensive biological assessment of the four macrourid species caught in South Georgia waters: Macrourus caml , Macrourus carinatus , Macrourus holotrachys and Macrourus whitsoni . Using fishery and observer data collected in 2018–2022, we reveal pronounced female‐biased sex ratios in three species ( M. holotrachys , M. carinatus and M. caml ), strong depth‐based segregation by body length, distinct distributions and habitat preferences related to environmental features (bathymetric depth and slope, primary productivity and temperature). By‐catch rates were highest in the southern region of South Georgia and varied across species: M. holotrachys was the most frequently caught and had a wide spatial and bathymetric distribution (∼1000–1750 m); M. caml was the second most caught and appeared the most flexible in terms of habitat use; M. carinatus was mainly caught in the west, including at Shag Rocks; and M. whitsoni was caught less frequently and in deeper water (> 1500 m), mostly in the northeast and east, and had the most restricted distribution. These interspecific differences underscore the need for species‐level assessments of fisheries risk and improved data collection to fill knowledge gaps. Overall, this study provides a critical foundation for understanding the ecology of Macrourus species in sub‐Antarctic ecosystems and highlights that additional data are required for by‐caught species to aid species‐level management in toothfish longline fisheries in the CCAMLR area.